KONFLIK BUDAYA AMERIKA DAN JEPANG DALAM FILM THE RAMEN GIRL - Iwan Sulistiawan; Tatat Haryati (Sekolah Tinggi Pariwisata Mataram, 2023)
This research attempts to identify the cultural conflicts depicted in The Ramen Girl (2008). Conflict in this study is defined as a clash that occurs between different values, beliefs, norms, or practices between groups or individuals who come from different cultural origins, in this case represented by Japanese and American culture, especially in the relationship between the two main characters, namely Abby, an American girl who after a conflict with her boyfriend, decided to stay in Japan to learn how to cook ramen and Maezumi, a Tokyo resident who owns a ramen shop who at first was against Abby's desire to learn from him. The research was conducted using an exploratory qualitative research method because it seeks to explore cultural conflicts between figures representing American culture and Japanese culture. The results of the study show that all the points from the essence of the conflict that originated from conflicting values, can be found in the interaction of the Abby vs Maezumi conflict. The conflicts that occur are mostly resolved by way of compromise, tolerance and mediation